Surds And Indices



 

 


Surds

A surd is a square root which cannot be reduced to a rational number.

For example,  is not a surd.

However  is a surd.

If you use a calculator, you will see that  and we will need to round the answer correct to a few decimal places. This makes it less accurate.

If it is left as , then the answer has not been rounded, which keeps it exact.

Here are some general rules when simplifying expressions involving surds.

 

 

 

  1. am x an = am + n
  2.  

am

am – n

an

 

 

  1. (am)n = amn

 

  1. (ab)n = anbn

 

  1.  

a

n

=

an

b

bn

 

 

 

 

 

 

  1. a0 = 1

 

 

Questions

Level-I

 

1. 

(17)3.5 x (17)? = 178

A.

2.29

B.

2.75

C.

4.25

D.

4.5

 

2. 

If

a

x – 1

=

b

x – 3

, then the value of x is:

b

a

A.

1

2

B.

1

C.

2

D.

7

2

 

3. 

Given that 100.48 = x, 100.70 = y and xz = y2, then the value of z is close to:

A.

1.45

B.

1.88

C.

2.9

D.

3.7

 

4. 

If 5a = 3125, then the value of 5(a – 3) is:

A.

25

B.

125

C.

625

D.

1625

 

5. 

If 3(x – y) = 27 and 3(x + y) = 243, then x is equal to:

A.

0

B.

2

C.

4

D.

6

 

.6. 

(256)0.16 x (256)0.09 = ?

A.

4

B.

16

C.

64

D.

256.25

 

7. 

The value of [(10)150 ÷ (10)146]

A.

1000

B.

10000

C.

100000

D.

106

 

8. 

1 

+

1

+

1

= ?

1 + x(b – a) + x(c – a)

1 + x(a – b) + x(c – b)

1 + x(b – c) + x(a – c)

A.

0

B.

1

C.

xa – b – c

D.

None of these

 

9. 

(25)7.5 x (5)2.5 ÷ (125)1.5 = 5?

A.

8.5

B.

13

C.

16

D.

17.5

E.

None of these

 

10. 

(0.04)-1.5 = ?

A.

25

B.

125

C.

250

D.

625

 

 

Level-II

 

11. 

(243)n/5 x 32n + 1

= ?

9n x 3n – 1

A.

1

B.

2

C.

9

D.

3n

 

12. 

1

+

1

= ?

1 + a(n – m)

1 + a(m – n)

A.

0

B.

1

2

C.

1

D.

am + n

 

13. 

If m and n are whole numbers such that mn = 121, the value of (m – 1)n + 1 is:

A.

1

B.

10

C.

121

D.

1000

 

14. 

xb

(b + c – a)

.

xc

(c + a – b)

.

xa

(a + b – c)

= ?

xc

xa

xb

A.

xabc

B.

1

C.

xab + bc + ca

D.

xa + b + c

 

15. If 5√5 * 53 ÷ 5-3/2 = 5a+2 , the value of a is:
A. 4       
B. 5       
C. 6       
D. 8

 

16.(132)7 ×(132)? =(132)11.5.

A. 3      
B. 3.5       
C. 4    
D. 4.5

 

 

17. (ab)x−2=(ba)x−7. What is the value   of x ?

 

A. 3      
B. 4    
C. 3.5     
D. 4.5

 

 

 

18. (0.04)-2.5 = ?

 

A. 125      
B. 25      
C. 3125  
D. 625

 

 

 

 

 

Answers

Level-I

Answer:1 Option D

 

Explanation:

Let (17)3.5 x (17)x = 178.

Then, (17)3.5 + x = 178.

 3.5 + x = 8

 x = (8 – 3.5)

 x = 4.5

 

Answer:2 Option C

 

Explanation:

Given 

a

x – 1

=

b

x – 3

b

a

a

x – 1

=

a

-(x – 3)

 = 

a

(3 – x)

b

b

b

 x – 1 = 3 – x

 2x = 4

 x = 2.

 

 

Answer:3 Option C

 

Explanation:

xz = y2        10(0.48z) = 10(2 x 0.70) = 101.40

 0.48z = 1.40

 z =

140

=

35

= 2.9 (approx.)

48

12

 

Answer:4 Option A

 

Explanation:

5a = 3125        5a = 55

 a = 5.

 5(a – 3) = 5(5 – 3) = 52 = 25.

 

 

Answer:5 Option C

 

Explanation:

3x  y = 27 = 33        x – y = 3 ….(i)

3x + y = 243 = 35        x + y = 5 ….(ii)

On solving (i) and (ii), we get x = 4

 

 

Answer:6 Option A

 

Explanation:

(256)0.16 x (256)0.09 = (256)(0.16 + 0.09)

   = (256)0.25

   = (256)(25/100)

   = (256)(1/4)

   = (44)(1/4)

   = 44(1/4)

   = 41

   = 4

Answer:7 Option B

 

Explanation:

(10)150 ÷ (10)146 =

10150

10146

   = 10150 – 146

   = 104

   = 10000.

 

Answer:8 Option B

 

Explanation:

Given Exp. =

1

 + 

1

 + 

1

1 +

xb

+

xc

xa

xa

1 +

xa

+

xc

xb

xb

1 +

xb

+

xa

xc

xc

   =

xa

+

xb

+

xc

(xa + xb + xc)

(xa + xb + xc)

(xa + xb + xc)

   =

(xa + xb + xc)

(xa + xb + xc)

   = 1.

 

Answer:9 Option B

 

Explanation:

Let (25)7.5 x (5)2.5 ÷ (125)1.5 = 5x.

Then,

(52)7.5 x (5)2.5

= 5x

(53)1.5

5(2 x 7.5) x 52.5

= 5x

5(3 x 1.5)

515 x 52.5

= 5x

54.5

 5x = 5(15 + 2.5 – 4.5)

 5x = 513

 x = 13.

 

Answer:10 Option B

 

Explanation:

(0.04)-1.5 =

4

-1.5

100

   =

1

-(3/2)

25

   = (25)(3/2)

   = (52)(3/2)

   = (5)2 x (3/2)

   = 53

   = 125.

 

Level-II

 

Answer:11 Option C

 

Explanation:

Given Expression

=

(243)(n/5) x 32n + 1

9n x 3n – 1

 

=

(35)(n/5) x 32n + 1

(32)n x 3n – 1

 

=

(35 x (n/5) x 32n + 1)

(32n x 3n – 1)

 

=

3n x 32n + 1

32n x 3n – 1

 

=

3(n + 2n + 1)

3(2n + n – 1)

 

=

33n + 1

33n – 1

 

= 3(3n + 1 – 3n + 1)   = 32   = 9.

Answer:12 Option C

 

Explanation:

1

+

1

=

1

 + 

1

1 +

an

am

1 +

am

an

1 + a(n – m)

1 + a(m – n)

   =

am

+

an

(am + an)

(am + an)

   =

(am + an)

(am + an)

   = 1.

 

Answer:13 Option D

 

Explanation:

We know that 112 = 121.

Putting m = 11 and n = 2, we get:

(m – 1)n + 1 = (11 – 1)(2 + 1) = 103 = 1000.

 

Answer:14 Option B

 

Explanation:

Given Exp.

 

x(b – c)(b + c – a) . x(c – a)(c +a – b) . x(a – b)(a + b – c)

 

x(b – c)(b + c) – a(b – c)  .  x(c – a)(c + a) – b(c – a)
   .  
x(a – b)(a + b) – c(a – b)

 

x(b2 – c2 + c2 – a2 + a2 – b2)  .   xa(b – c) – b(c – a) – c(a – b)

 

= (x0 x x0)

 

= (1 x 1) = 1.

 

Answer:15 option C

 

Answer:16 

Explanation

am.an=am+n

(132)7 × (132)x = (132)11.5

=> 7 + x = 11.5

=> x = 11.5 – 7 = 4.5

 

 

Answer:17 

Explanation:

an=1a−n

(ab)x−2=(ba)x−7(ab)x−2=(ab)−(x−7)x−2=−(x−7)x−2=−x+7x−2=−x+72x=9x=92=4.5

 

Answer:18 

Explanation:

a−n=1/an

(0.04)−2.5=(1/.04)2.5=(100/4)2.5=(25)2.5=(52)2.5=(52)(5/2)=55=3125

 

 


error: Content is protected !!